Is there a common linkage among reading comprehension, visual attention, and magnocellular processing? - Solan HA; Shelley-Tremblay JF; Hansen PC; Larson S (Journal of Learning Disabilities)
The authors examined the relationships between reading comprehension, visual attention, and magnocellular processing in 42 Grade 7 students. The goal was to quantify the sensitivity of visual attention and magnocellular visual processing as concomitants of poor reading comprehension in the absence of either vision therapy or cognitive intervention. Nineteen good readers (M = grade equivalent of 11.2) and 23 poor readers (M = grade equivalent of 3.5) were identified. Participants were tested for visual attention skills (Cognitive Assessment System: CAS) and magnocellular integrity (Coherent Motion Threshold: CM). Individual and combined correlations of dependent variables with reading were significant at the 0.01 level. When combined, the two tests (CAS + CM) accounted for 61% of the variance in reading comprehension. Logistic regression analysis measured sensitivity of the two diagnostic tests. Attention tests correctly classified 95.7% of poor readers, and coherent motion correctly classified 78.3% of poor readers. When the data were combined, 91.3% of poor readers were correctly classified. The research reinforces the notion that a common linkage exists between reading comprehension, visual attention, and magnocellular processing. Diagnostic test batteries for students who have been identified as reading disabled should include magnocellular and visual attention tests. Procedures to diagnose and ameliorate these disabilities are discussed.